Я привлекаю деньги - Правдина Наталия Борисовна (Деньги, карьера, успех, 2003)
Экземпляры: аб. (2003) / Инвентарный номер: 47554 / Цена: / Сис.шифр: 88.5 / Авт.знак: П 68 / ГРНТИ: 15.41.51 / ББК: 88.5